Konvencionalisti in kontekstualisti: cambriška šola interpretacije med avtorjem in bralcem - Pikalo, Jernej (Teorija in praksa, 2007)
Article critically examines two dominant approaches of the Cambridge School of Political Thought: conventionalist and contextualist. Conventionalist and contextualist tradition are predominantly focused on author and its intentions, and less on reader or interpreter of political ideas. The article calls for dialogical approach to interpreting of political ideas. The meaning of political ideas should be established in a dialogue between the author and the reader. The article analyses development, points of agreement and disagreement of the Cambridge school approaches.
Keywords: Political ideas; Politične ideje; Zgodovina; History; interpretacija